What factors influencing purchasing decisions for cosmetic products? A study on brand image, price, and promotion - Novi Safitri; Muhammad Amirudin Syarif (Journal of Enterprise and Development (JED), 2023)
Purpose — This study aims to investigate the factors influencing the purchasing decisions of cosmetic products, particularly focusing on the impact of brand image, price, and promotion, in the context of increasing global competition and the importance of maintaining product brand image.Method — This study focused on consumers in Palembang who use cosmetic products. We included 96 respondents chosen through the Accidental Sampling technique, collecting data via distributed questionnaires. Our analysis utilized SEM (Structural Equation Modeling) with SmartPLS 3.0 software.Result — The research findings show that brand image does not have a significant impact on purchasing decisions. However, the price and promotion variables were found to significantly influence purchasing decisions.Contribution — This study contributes to the existing literature by specifically examining the factors influencing purchasing decisions for cosmetic products in the context of Palembang. The novel aspect of this research lies in its analysis of the interplay between brand image, price, and promotion within this specific market, shedding light on the unique dynamics that may differ from broader studies in other regions.